2015
DOI: 10.4049/jimmunol.1401938
|View full text |Cite
|
Sign up to set email alerts
|

T Follicular Helper, but Not Th1, Cell Differentiation in the Absence of Conventional Dendritic Cells

Abstract: Development of long-lived humoral immunity is dependent on CXCR5-expressing T follicular helper (Tfh) cells, which develop concomitantly to effector Th cells that support cellular immunity. Conventional dendritic cells (cDCs) are critical APCs for initial priming of naive CD4+ T cells but, importantly, also provide accessory signals that govern effector Th cell commitment. To define the accessory role of cDCs during the concurrent development of Tfh and effector Th1 cells, we performed high-dose Ag immunizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 61 publications
1
17
0
Order By: Relevance
“…Indeed, an elegant study by Chakarov and Fazilleau 128,129 demonstrated that, similarly to cDCs [130][131][132][133][134][135][136] , Toll-like receptor 9 (TLR9)-stimulated monocytes directly present antigen and induce the differentiation of T FH cells via IL-6 production. Another study using a high-dose antigen regimen suggested that in the absence of cDCs, LY6C + monocytes (along with B cells) induce T FH cell development 137 . The question that follows is which T FH cell population is affected by the lack of monocytes?…”
Section: Antigen-presenting Monocytes Induce T Fh Cellsmentioning
confidence: 99%
“…Indeed, an elegant study by Chakarov and Fazilleau 128,129 demonstrated that, similarly to cDCs [130][131][132][133][134][135][136] , Toll-like receptor 9 (TLR9)-stimulated monocytes directly present antigen and induce the differentiation of T FH cells via IL-6 production. Another study using a high-dose antigen regimen suggested that in the absence of cDCs, LY6C + monocytes (along with B cells) induce T FH cell development 137 . The question that follows is which T FH cell population is affected by the lack of monocytes?…”
Section: Antigen-presenting Monocytes Induce T Fh Cellsmentioning
confidence: 99%
“…While Tfh cell differentiation is generally abrogated in the absence of DCs as antigen-presenting cells, 14 Tfh cells may be primed in the absence of DCs under certain conditions, such as high antigen availability. [15][16][17] Even though it is known that DCs provide critical co-stimulatory signals to the T cells via activation of CD28, [18][19][20] is mediated by several chemokine receptors expressed by these cells. Additional signaling circuits that regulate Tfh cell generation depend on local cytokine concentrations.…”
Section: Tfhcellprimingbydendriticcellsmentioning
confidence: 99%
“…In comparison to signals that regulate the B–Tfh cell interaction relatively little is known about the signals required to generate Tfh cells during the first DC–T‐cell interaction. However, in conditions of high antigen dose such as viral infection, DC are dispensable for the generation of Tfh cells, suggesting that they are only essential when the amounts of antigen are limiting . The mode of antigen presentation, the co‐receptors and the cytokines expressed by DC are key determinants of Tfh cell differentiation.…”
Section: The Role Of Antigen Presentation In Tfh Cell Differentiationmentioning
confidence: 99%
“…However, in conditions of high antigen dose such as viral infection, DC are dispensable for the generation of Tfh cells, suggesting that they are only essential when the amounts of antigen are limiting. 27,28 The mode of antigen presentation, the co-receptors and the cytokines expressed by DC are key determinants of Tfh cell differentiation. Further rounds of antigenic stimulation in the second phase of Tfh cell differentiation, usually mediated by B cells, are required to stabilize Bcl6 expression and complete Tfh cell differentiation.…”
Section: Presentation Of Antigen By DCmentioning
confidence: 99%